A novel deployable tied arch bridge - Lederman, G; You, Z; Glisic, B (Elsevier, 2014)
This paper presents a novel type of vehicle launched deployable bridge for military or relief operations. Most existing vehicle launched deployable bridges (also known as assault bridges or mobile bridges) take the form of a simply supported beam and require mechanically complex deployment sequences. This bridge has, first, an innovative deployment sequence based on a single actuator and a tied arch form; second, a stackable cross-section to reduce the package size during transport; and third, vertical suspenders which allow for “smart” redistribution of load as the bridge deflects. Analysis of the bridge is presented along with experimental results from a three-meter long scale physical model. Load cells and fiber optic strain sensors are used to monitor the physical model, and the results are shown in relation to a statics analysis. Our results suggest this novel design would have lower forces and moments than existing deployable bridges, making it lighter and potentially advancing the current state of the art.